2018
DOI: 10.1016/j.yebeh.2018.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitudes towards epilepsy among teachers: A systematic review

Abstract: The objective of this study was to systematically review research that has focused on knowledge of and attitudes towards epilepsy among teachers. Embase, PubMed, PsycINFO, Google Scholar, and Cochrane library databases from 2000 to 2017 were searched. Cross-sectional and interventional studies were included and analyzed for quality. Thematic analysis was used to identify common themes in the results. Fifty-four eligible studies (17,256 total participants in 27 different countries) were identified in the search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 73 publications
1
29
0
1
Order By: Relevance
“…Epilepsi konusunda yapılan birçok çalışmada hem hastalar hem de toplum açısından bilginin önemi ısrarla vurgulanmaktadır. [32][33][34][35][36][37] Ancak, bu çalışmada güvenlik alt boyutunun bilgi ölçeği ile negatif korelasyon göstermesi dikkat çekicidir. Bu durum, yüksek bilgi düzeyinin hastaların özgüvenlerini artırarak güvenlik konusunda daha dikkatsiz davranmalarına neden olması ile açıklanabilir.…”
Section: Discussionunclassified
“…Epilepsi konusunda yapılan birçok çalışmada hem hastalar hem de toplum açısından bilginin önemi ısrarla vurgulanmaktadır. [32][33][34][35][36][37] Ancak, bu çalışmada güvenlik alt boyutunun bilgi ölçeği ile negatif korelasyon göstermesi dikkat çekicidir. Bu durum, yüksek bilgi düzeyinin hastaların özgüvenlerini artırarak güvenlik konusunda daha dikkatsiz davranmalarına neden olması ile açıklanabilir.…”
Section: Discussionunclassified
“…This may reflect teachers' natural tendency to rely on academic achievements when evaluating a child's behavior, or their use of age-appropriate comparison groups when making such evaluations [63]. However, a recent systematic review on teachers' attitudes towards epilepsy indicated that deficits in knowledge and negative attitudes were relatively common [64]. Thus, it is important to address the differences between informants' perceptions when planning EBP interventions in the schools or within rehabilitation settings.…”
Section: Mediation Model Of Cognitive Functioning and Child's Emotionmentioning
confidence: 99%
“…Several studies have generally demonstrated lack of knowledge about seizures management and negative attitudes in teachers and students, with a deep influence on quality of life and social inclusion of subjects with epilepsy, above all in children attending school [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, Italian teachers do not receive any formal education about medical disorders, including epilepsy, and numerous studies have demonstrated that teachers have inadequate training, misunderstand the disease and are not able to correctly handle a seizure. Furthermore, teachers, in general, underestimate the academic abilities of students with epilepsy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%